PERATURAN BUPATI LAMPUNG TIMUR NO. 37 TAHUN 2019 TENTANG PEDOMAN PELAKSANAAN PELAYANAN KESEHATAN GRATIS: LESSON LEARNED DI RSUD SUKADANA - Nuryanti, Fatmi; Majid, Nurkholis; Fitriani, Yuyun; Prihantika, Ita; Lendra, I Wayan (Jurnal Analisis Sosial Politik, 2020)
Implementation of East Lampung Regent’s Regulation No. 37 of 2019 concerning Guidelines for Implementing Free Health Services for the Community at Sukadana District Hospital is experiencing various problems ranging from the large number of people who do not yet know about the existence of free treatment due to lack of outreach to the limited budget provided by the East Lampung Regency government . The method in this research uses a qualitative method.Based on the research, it can be concluded that: (1) Guidelines for the Implementation of the Free Health Service Program for the Community of East Lampung at the Sukadana Hospital, East Lampung Regency, have not run according to expectations and have not been achieved optimally. (2) Sukadana Regional Hospital as the medical health facilitator appointed by the East Lampung district government already has adequate facilities and infrastructure, but Sukadana Regional Hospital must also approach the community so that the community understands and understands the Community Health Service Program for the East Lampung community.